Pediatric Ovarian Torsion: A Diagnostic Challenge in COVID-19 Times - Chanchlani, R.; Jangid, M.; Ahmad, R.; Sharma, P. (Kathmandu University Medical Journal, 2020)
Ovarian torsion is a rare gynecological emergency in children and an early surgical intervention is needed to salvage the ovary. Herein, we present a case of eight year old girl who presented with complaints of lower abdominal pain during ongoing COVID-19 pandemic. She was diagnosed as a case of ovarian torsion on right side. She underwent exploratory laparotomy and ovarian cystectomy was performed. Delay in diagnosis and treatment of ovarian torsion may have grave consequences, resulting in functional loss of the ovary.